Effects of growth stage on the fermentation quality, microbial community, and metabolomic properties of Italian ryegrass (Lolium multiflorum Lam.) silage - Fu, Zhihui; Sun, Lin; Wang, Zhijun; Liu, Jingyi; Hou, Meiling; Lu, Qiang; Hao, Junfeng; Jia, Yushan; Ge, Gentu (Frontiers in Microbiology, 2023)
This study aimed to investigate the effects of different growth stages (booting period-SYK; initial flowering-SCK; full flowering-SSK) on the fermentation quality, microbial community, metabolic pathways and metabolomic characteristics of Italian ryegrass silage. Single molecule real-time (SMRT) sequencing and ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS/MS) were used to analyze bacterial communities and metabolites, respectively. After 60 d of fermentation, SYK had the lowest pH and the highest lactic acid content, which were significantly different from the other groups. The bacteria with the highest abundance in SYK, SCK and SSK groups were Lactiplantibacillus plantarum (63.98%), Weissella minor (28.82%) and Levilactobacillus brevis (64.81%), respectively. In addition, among the main differential metabolites in different growth stages, the number of amino acids was the most, and the corresponding metabolic pathways were mainly amino acid metabolic pathways. The biosynthesis of phenylalanine, tyrosine and tryptophan was significantly enriched (p<0.01) at booting stage and full flowering stage. Purine metabolism and ABC transporter pathway were significantly enriched at the initial flowering (p<0.001). Lactiplantibacillus plantarum had a negative correlation with xanthine and ganoderic acid F. Weissella minor had a positive correlation with D-Mannose and ganoderic acid F. Levilactobacillus brevis had a positive correlation with xanthine, and Latilactobacillus sakei had a positive correlation with cinnamic acid, D-Mannose, 2-Hydroxycinnamic acid and uridine. In conclusion, this study reveals the interaction mechanisms between ryegrass raw materials at different growth stages and epiphytic microorganisms during ensiling fermentation, providing new ideas for screening functional lactic acid bacteria, and laying a theoretical foundation for the production of safe and high-quality silage.